PLANT IMPACT ON THE BIOGEOCHEMICAL CYCLE OF SILICON AND RELATED WEATHERING PROCESSES - Alexandre A.; Meunier J.D.; Colin F.; Koud J.M. (My University, 1997)
The contribution of plants to the biogeochemical cycle of Si and related weathering processes was studied in an equatorial rainforest ecosystem (Congo) where the biologic turnover of Si is high (58 to 76 kg/ha/y). Litterfall leaves, a soil profile and groundwaters were analysed. Phytoliths and organic matter have a similar distribution with depth in the soil profile. The model of a bicompartmental distribution of organic matter is applied to phytolith distribution and shows that about 92% of the biogenic silica input is rapidly recycled while about 8% of the biogenic silica input supplies a stable pool of phytoliths, with a lower turnover. Reprecipitation of silica was observed at the base of the soil profile, indicating a local geochemical environment that is oversaturated with respect to amorphous silica. A balance in biogeochemical cycle of Si requires that the vegetation absorb dissolved silicon released from weathering of minerals, which otherwise would be available for mineral neoformation or export from the profile towards regional drainages. Plant uptake of Si increases the chemical weathering rate without increasing the denudation rate. This study shows that the uptake, storage, and release of Si by the vegetation have to be taken into account when using dissolved Si for tracing chemical weathering dynamics.